2020
DOI: 10.1063/1.5131753
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of the triplet state electronic structure of free-base 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin by a combined advanced EPR and theoretical approach

Abstract: The nature of the photoexcited triplet state of free-base 5,10,15,20-tetrakis(4-sulfonatophenyl)porphyrin (H2TPPS4−) has been investigated by advanced Electron Paramagnetic Resonance (EPR) techniques combined with quantum chemical calculations. The zero-field splitting (ZFS) parameters, D and E, the orientation of the transition dipole moment in the ZFS tensor frame, and the proton hyperfine couplings have been determined by magnetophotoselection-EPR and pulse electron-nuclear double resonance spectroscopy. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 89 publications
3
27
0
Order By: Relevance
“…The orientation selection effect caused by the polarization of the laser light (parallel/perpendicular to the external field) causes changes to the intensities of the EPR transitions. 29 , 42 , 43 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…The orientation selection effect caused by the polarization of the laser light (parallel/perpendicular to the external field) causes changes to the intensities of the EPR transitions. 29 , 42 , 43 , 50 …”
Section: Resultsmentioning
confidence: 99%
“…The spectral analysis allows to define the relative orientation between the optical TDM and the ZFS principal axes [27]. Magnetophotoselection, applied to porphyrin systems, has been used in a limited number of cases to attain quantitative information on the relative orientation of the ZFS tensor axes with respect to the TDM, if one of the two is known [35,45]. Spectral simulations require the correct formalism to take into account potential dynamic Jahn-Teller effects in the specific case of ZnPP.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that magnetophotoselection is a key spectroscopic tool in providing valuable information on the electronic structure of the porphyrin molecule in the excited states and assessing the corresponding symmetry. Combining optical and magnetic selection, the information is not confined to the paramagnetic triplet state, but it is extended to the corresponding excited singlet state connected by the intersystem crossing mechanism, as already highlighted in previous work in the case of free-base porphyrins, where a phototautomerization process is occurring [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This likely indicates either that the laser power used was sufficient to saturate the transition and excite both Q x and Q y , or that phototautomerism of the indole protons exchanges the Q x and Q y by a pseudorotation, making the directions of the transition dipole moment indistinguishable in the porphyrin plane. 60 Furthermore, no magneto-photoselection effects were recorded under the conditions of these experiments as minimal differences were seen in both field sweep spectra or ReLaserIMD traces recorded with the laser polarization horizontal and vertical to B 0 (see Figure S3 ). Because the optical transition frame aligns with the ZFS splitting frame generated in the triplet state, as the Q x and Q y are interchangeable, the correlation between the g tensor of the nitroxide and the ZFS frame is lost.…”
Section: Orientation Selection In Relaserimdmentioning
confidence: 86%